2014
DOI: 10.1179/1743284713y.0000000248
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nd on microstructure and mechanical properties of Mg–Al–Ca alloy

Abstract: Effects of Nd additions (0–4 wt-) on microstructures and properties of Mg–Al–Ca alloy at room temperature and 150°C have been investigated. The results showed that Mg–6Al–2Ca alloy consisted of α-Mg matrix, Mg17Al12, Mg–Ca and Al–Ca phases. The amount of Al–Nd phase increases with the increasing of Nd content while that of Mg17Al12 decreases. On the other hand, Nd refines the microstructure of as cast and extruded alloys. The ultimate strength and yield strength of experimental alloys are improved with the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Yamasaki et al [26] found that the yield strength of the warm-extruded magnesium alloy Mg-Zn-2.5Gd reached a high level of 345 MPa, because of the refinement of grains and the dispersion of a precipitate with a long period ordered (LPO) structure. Chen et al [27] On the other hand, as mentioned earlier, with the addition of alloying elements to magnesium, the extrudability usually decreases [11]. Luo et al [28], for example, found that the incipient melting point of the magnesium alloy AZ31 was 371 K (98 °C) lower than that of AM30 due to the presence of Zn in the former.…”
Section: Introductionmentioning
confidence: 99%
“…Yamasaki et al [26] found that the yield strength of the warm-extruded magnesium alloy Mg-Zn-2.5Gd reached a high level of 345 MPa, because of the refinement of grains and the dispersion of a precipitate with a long period ordered (LPO) structure. Chen et al [27] On the other hand, as mentioned earlier, with the addition of alloying elements to magnesium, the extrudability usually decreases [11]. Luo et al [28], for example, found that the incipient melting point of the magnesium alloy AZ31 was 371 K (98 °C) lower than that of AM30 due to the presence of Zn in the former.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [73] also observed that Mg-5Al-0.3Mn-1.5Ce alloy exhibited the best tensile strength due to the presence of optimized content of Al11Ce3 + β-Mg17Al12. Chen et al [74] reported that the addition of Nd led to the formation of higher melting Al-Nd intermetallic and also improved the room temperature strength of the Mg-6Al-2Ca-xNd (x = 1,2) alloys. Wu et al [75] reported that the addition of REs and Ca to AZ91 alloys led to the improvement in strength as well as corrosion resistance due to the presence of Al2Ca phases.…”
Section: Mg-al-re Higher Alloy Systemsmentioning
confidence: 99%
“…Moreover, solid-solution hardening was possible due to the lower difference between atomic radii of the Mg and Nd elements. 64 In addition to this, the divorced eutectic β-phase results in precipitation hardening of α-matrix, which enhances the strength of the composite. The development of the secondary phase of Nd and HAP on the grain boundaries provides the necessary resistance to the grain growth and pinning dislocation movement.…”
Section: Discussionmentioning
confidence: 99%